2016
DOI: 10.1517/14740338.2016.1139571
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of and attitudes towards receiving information about non-steroidal anti-inflammatory drugs: a cross-sectional survey of patients in Thailand

Abstract: Patients received medicines information mostly from healthcare professionals, but safety information was limited. Type of NSAIDs, regularity of NSAID use and age affected receipt of safety information about NSAIDs. Provision of more medicine information is needed, particularly written documents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 40 publications
2
31
1
1
Order By: Relevance
“…Information communicated to patients using NSAIDS varied between different health professionals, but also depended on type of NSAID and duration of use. Pharmacists in both hospital and community provided general information on administration and indication, which was consistent with our previous survey of NSAID users, a high proportion of whom reported receiving such information . However, the present study suggests physicians did not always offer this information, which may contribute to the apparent confusion, mentioned by some pharmacists.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Information communicated to patients using NSAIDS varied between different health professionals, but also depended on type of NSAID and duration of use. Pharmacists in both hospital and community provided general information on administration and indication, which was consistent with our previous survey of NSAID users, a high proportion of whom reported receiving such information . However, the present study suggests physicians did not always offer this information, which may contribute to the apparent confusion, mentioned by some pharmacists.…”
Section: Discussionsupporting
confidence: 87%
“…Patients on the other hand have indicated that, while the majority receive information about how to use NSAIDs and their indication, fewer than half report receiving information about side effects and they perceive the risks of NSAIDs as generally low . The findings from this survey do, however, concur with those of health professionals, in that attitudes towards receiving written information in the form of PILs were positive . Such leaflets are not, however, widely available in Thailand, despite evidence that they can improve patient knowledge of medicines .…”
Section: Introductionmentioning
confidence: 47%
See 3 more Smart Citations